Wywiad rzeka jako proces. Archiwum osobiste Barbary Skargi - Dziel, Paweł (Acta Universitatis Lodziensis. Folia Litteraria Polonica, 2022)
The article’s primary purpose is to discuss the process of creating the extended interview titled “Innego końca świata nie będzie”. Z Barbarą Skargą rozmawiają Katarzyna Janowska i Piotr Mucharski [En. “There will be no Other End of the World”. Katarzyna Janowska and Piotr Mucharski Are Talking with Barbara Skarga], published in 2007. The analysis refers to Barbara Skarga`s personal archive, which is available at the Joint Libraries of the Faculty of Philosophy and Sociology of the University of Warsaw, the Institute of Philosophy and Sociology of the Polish Academy of Sciences, and the Polish Philosophical Society. Archival materials related to this ‘spoken book’ involve mainly computer printouts with handwritten deletions, notes, and additions. The article also includes the philosopher’s typescripts related to her academic activity. Studying the process of shaping the conversation in Innego końca świata nie będzie… leads to more general conclusions about the style of Barbara Skarga’s language. Conclusions indicating the type of subjectivity revealed in the interview were also used to discuss the author’s essays.